Direct Oral Anticoagulants Versus Warfarin in Patients With Atrial Fibrillation: Patient-Level Network Meta-Analyses of Randomized Clinical Trials With Interaction Testing by Age and Sex. Issue 4 (25th January 2022) - Carnicelli, Anthony P.; Hong, Hwanhee; Connolly, Stuart J.; Eikelboom, John; Giugliano, Robert P.; Morrow, David A.; Patel, Manesh R.; Wallentin, Lars; Alexander, John H.; Cecilia Bahit, M.; Benz, Alexander P.; Bohula, Erin A.; et al.
Abstract : Background: Direct oral anticoagulants (DOACs) are preferred over warfarin for stroke prevention in atrial fibrillation. Meta-analyses using individual patient data offer substantial advantages over study-level data. Methods: We used individual patient data from the COMBINE AF (A Collaboration Between Multiple Institutions to Better Investigate Non-Vitamin K Antagonist Oral Anticoagulant Use in Atrial Fibrillation) database, which includes all patients randomized in the 4 pivotal trials of DOACs versus warfarin in atrial fibrillation (RE-LY [Randomized Evaluation of Long-Term Anticoagulation Therapy], ROCKET AF [Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared With Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation], ARISTOTLE [Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation], and ENGAGE AF-TIMI 48 [Effective Anticoagulation With Factor Xa Next Generation in Atrial Fibrillation–Thrombolysis in Myocardial Infarction 48]), to perform network meta-analyses using a stratified Cox model with random effects comparing standard-dose DOAC, lower-dose DOAC, and warfarin. Hazard ratios (HRs [95% CIs]) were calculated for efficacy and safety outcomes. Covariate-by-treatment interaction was estimated for categorical covariates and for age as a continuous covariate, stratified by sex. Results: A total of 71 683 patients were included (29 362 on standard-dose DOAC, 13 049 on lower-dose DOAC, and 29 272 on warfarin). Compared with warfarin, standard-dose DOACs were associated with a significantly lower hazard of stroke or systemic embolism (883/29 312 [3.01%] versus 1080/29 229 [3.69%]; HR, 0.81 [95% CI, 0.74–0.89]), death (2276/29 312 [7.76%] versus 2460/29 229 [8.42%]; HR, 0.92 [95% CI, 0.87–0.97]), and intracranial bleeding (184/29 270 [0.63%] versus 409/29 187 [1.40%]; HR, 0.45 [95% CI, 0.37–0.56]), but no statistically different hazard of major bleeding (1479/29 270 [5.05%] versus 1733/29 187 [5.94%]; HR, 0.86 [95% CI, 0.74–1.01]), whereas lower-dose DOACs were associated with no statistically different hazard of stroke or systemic embolism (531/13 049 [3.96%] versus 1080/29 229 [3.69%]; HR, 1.06 [95% CI, 0.95–1.19]) but a lower hazard of intracranial bleeding (55/12 985 [0.42%] versus 409/29 187 [1.40%]; HR, 0.28 [95% CI, 0.21–0.37]), death (1082/13 049 [8.29%] versus 2460/29 229 [8.42%]; HR, 0.90 [95% CI, 0.83–0.97]), and major bleeding (564/12 985 [4.34%] versus 1733/29 187 [5.94%]; HR, 0.63 [95% CI, 0.45–0.88]). Treatment effects for standard- and lower-dose DOACs versus warfarin were consistent across age and sex for stroke or systemic embolism and death, whereas standard-dose DOACs were favored in patients with no history of vitamin K antagonist use ( P =0.01) and lower creatinine clearance ( P =0.09). For major bleeding, standard-dose DOACs were favored in patients with lower body weight ( P =0.02). In the continuous covariate analysis, younger patients derived greater benefits from standard-dose (interaction P =0.02) and lower-dose DOACs (interaction P =0.01) versus warfarin. Conclusions: Compared with warfarin, DOACs have more favorable efficacy and safety profiles among patients with atrial fibrillation. Abstract : Supplemental Digital Content is available in the text.